Message Structure and Mechanism in Hypnotherapy Communication - Tarsani TARSANI; Arief SUBHAN; Dewi WIDOWATI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The purpose of this study is to describe, analyze, structure and mechanism of messages as well as models of interpersonal communication carried out in hypnotherapy as a method to overcome the problems felt by clients who experience psychosomatic health disorders including stress, mental disorders, emotions and subconscious mind control so that appropriate treatment is needed. The theory used in this research is Coordinated Management of Meaning (CMM) to analyze the communication interaction between the hypnotherapist and the client. There are three concepts in CMM, namely management, coordination, and meaning. The research method used is descriptive qualitative method with a case study approach and constructivist paradigm. The results showed that the structure and mechanism of messages in hypnotherapy communication were carried out is the messages produced were carried out in an implicit way, making arguments at the beginning of handling cases the hypnotherapist puts himself in a position to accept whatever is conveyed or claimed and the persuasive message conveyed by the therapist is a one-sided message. In the process of compiling and delivering messages: the message is based on Milton Erickson's principles and philosophy, use indirect style and using Metaphors. While the Communication Model used in Ericksonian Hypnotherapy Communication consists of message design models and interpersonal models. Message design is based on three basic logics of communication message design expressive, conventional, and rhetorical. The interpersonal model consists of social exchange, role, and interactional. Model of CMM theory produces the concept of BIER (Believe, Impressif, Entertaint, Repeatation) and sense making